New “improved” Compton scatter tomography modality for investigative imaging of one-sided large objects - Cebeiro, Javier (2017)
In an effort to promote Compton scatter tomography (CST) as an adequate modality for imaging the inner parts of large objects limited in a half-space of ℝ, we show that the standard CST can be ‘improved’ in some particular sense by ‘doubling’ the scanning mechanism. To this end, one needs to record for each position of a detector the scattered flux densities at two energies of scattered radiation, instead of one. Curiously, thanks to geometric inversion, this ‘double’ scanning may be converted into a transmission scanning on an apparent object, not along a straight line path as usual, but along a folded line in the shape of a V-line path. It has been proved that this V-line transmission scanning admits a well-defined reconstruction procedure. Therefore, the proposed CST with ‘double’ scanning, which solves the above imaging inverse problem, shows an ‘improved’ reconstructed image as compared to the standard one. We present theoretical arguments to support this claim as well as numerical simulations to illustrate its working and its viability.